1999
DOI: 10.1046/j.1432-1327.1999.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel human DNA‐binding protein with sequence similarity to a subfamily of redox proteins which is able to repress RNA‐polymerase‐III‐driven transcription of the Alu‐family retroposons in vitro

Abstract: In this study we identified a novel protein which may contribute to the transcriptional inactivity of Alu retroposons in vivo. A human cDNA clone encoding this protein (ACR1) was isolated from a human expression library using South-western screening with an Alu subfragment, implicated in the regulation of Alu in vitro transcription and interacting with a HeLa nuclear protein down-regulated in adenovirus-infected cells. Bacterially expressed ACR1 is demonstrated to inhibit RNA polymerase III (Pol III)-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 71 publications
(103 reference statements)
1
49
0
Order By: Relevance
“…Many Alu sequences are transcribed by RNA polymerase III, and this transcription is regulated by many RNA polymerase III transcription factors (20). One of these factors is an ϳ23-kDa Alu-co-repressor protein ACR1 (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many Alu sequences are transcribed by RNA polymerase III, and this transcription is regulated by many RNA polymerase III transcription factors (20). One of these factors is an ϳ23-kDa Alu-co-repressor protein ACR1 (20).…”
Section: Discussionmentioning
confidence: 99%
“…ACR1 protein may still bind to it and mediate the masking of the E2-box from being bound by SLUG repressor protein. Apart from ACR1, the polymerase II transcription factor YY1 may also bind to the same sequence of the Alu element (20,28) and thus, has the potential to add to the desilencing mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,10 PRDX5, previously named PrxV, AOEB166, PMP20 or ACR1, is the last member of mammalian PRDXs that has been cloned and characterized. 12,[18][19][20][21][22] Human PRDX5 can be addressed to several subcellular compartments such as mitochondria, peroxisomes, the nucleus and the cytosol. 12,[18][19][20][21] In a previous report, we presented a crystal structure of human PRDX5 in its reduced form.…”
Section: Figure 1 (A) Topological Diagram Showing the Arrangement Ofmentioning
confidence: 99%
“…12,[18][19][20][21][22] Human PRDX5 can be addressed to several subcellular compartments such as mitochondria, peroxisomes, the nucleus and the cytosol. 12,[18][19][20][21] In a previous report, we presented a crystal structure of human PRDX5 in its reduced form. 22 The structure revealed that peroxidatic Cys47 and resolving Cysl51 were too distant to form an intramolecular disulfide bond upon oxidation without important conformational changes.…”
Section: Figure 1 (A) Topological Diagram Showing the Arrangement Ofmentioning
confidence: 99%